Analyses of phytochemicals and nutritional compositions in Bambara groundnut (Vigna subterranea [L.] Verdc) - Nomathemba Gloria Majola; Abe Shegro Gerrano; Hussein Shimelis; Jacob Mashilo (Journal of Agriculture and Food Research)
Bambara groundnut (Vigna subterranea (L.) Verdc) grains have variable phytochemical compositions and minerals vital for the food and feed industry. There is a need to exploit the genetic diversity of Bambara groundnut for breeding new varieties with enhanced seed yield, nutritional content and quality to develop various products. The objective of this study was to determine the compositions of phytochemicals and mineral elements present in Bambara groundnut genetic pool to identify superior and contrasting genotypes to guide product development and breeding. Seventy-five genetically diverse Bambara groundnut genotypes were field evaluated across four locations (Brits, Loskop, Mafikeng and Polokwane) using a 15 × 5 alpha lattice design with three replications during the 2020–2021 cropping season. Genotypes were profiled for fat, phenolic and flavonoids contents at the Agricultural Research Council (ARC) analytical laboratory in South Africa. Further, the genotypes were assessed for the contents of the following minerals: calcium (Ca), iron (Fe), potassium (K), phosphorus (P), zinc (Zn) and nitrogen (N). The nutritional content of the test genotypes varied significantly (P < 0.05), which were affected by the genotype-by-environment interactions. These suggested genotypes could be selected for the suitability for cultivation and recommendation to each environment. The Ca, Fe, K and Zn content varied from 150.70 to 216.53, 4.30 to 16.77, 771.99 to 1155.89 and 5.50–7.17 mg/100 g dry seed sample, respectively. Genotypes, including ARC Bamb-2, ARC Bamb-19, ARC Bamb-73, ARC Bamb-56, ARC Bamb-37, ARC Bamb-3 and ARC Bamb-69 exhibited the highest fat content (>6.00 %). ARC Bamb-40 and ARC Bamb-59 recorded a higher mean Fe content of 16.00 mg.100 g−1. ARC Bamb-2 was the top-performing genotype with high fat content (6 %), Ca (211.93 mg.100 g−1), and Zn (7.17 mg/100 g). Ca,K, and N contents displayed strong correlations (r > 0.60, P < 0.05). Phosphorus and Zn contents exhibited moderate correlations with Ca. Overall, the study selected genotypes ARC Bamb-73, ARC Bamb-19, ARC Bamb-9 and ARC Bamb-2 with high compositions of essential nutrients for product development or breeding. The selected genetic resources are valuable for trait integration and developing new breeding populations with enhanced nutrient compositions and agronomic and market-preferred traits.